2009
DOI: 10.1093/eurheartj/ehp034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plaque components on no-reflow phenomenon after stent deployment in patients with acute coronary syndrome: a virtual histology-intravascular ultrasound analysis

Abstract: AimsWe used virtual histology-intravascular ultrasound (VH-IVUS) to evaluate the relation between coronary plaque characteristics and no-reflow in acute coronary syndrome (ACS) patients.Methods and resultsA total of 190 consecutive ACS patients were imaged using VH-IVUS and analysed retrospectively. Angiographic no-reflow was defined as TIMI flow grade 0, 1, and 2 after stenting. Virtual histology-intravascular ultrasound classified the colour-coded tissue into four major components: fibrotic, fibro-fatty, den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 33 publications
2
81
1
1
Order By: Relevance
“…Plaque rupture, which is another common sign of plaque instability, has been found to be closely related to noreflow in patients with ST-segment elevation myocardial infarction. 24,25 In addition, the fibrofatty volume detected by VH-IVUS and lipid-rich plaque assessed by IB-IVUS have been reported to be important predictors of coronary no-reflow after PCI, 4,14 while others have shown that only the percentage of necrotic core and thincap fibroatheroma were predictive of noreflow after PCI. 26 These discrepancies may be attributable to the different patient populations, as some studies were performed in patients with acute myocardial infarction, while others included both patients with acute myocardial infarction and those with unstable angina.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque rupture, which is another common sign of plaque instability, has been found to be closely related to noreflow in patients with ST-segment elevation myocardial infarction. 24,25 In addition, the fibrofatty volume detected by VH-IVUS and lipid-rich plaque assessed by IB-IVUS have been reported to be important predictors of coronary no-reflow after PCI, 4,14 while others have shown that only the percentage of necrotic core and thincap fibroatheroma were predictive of noreflow after PCI. 26 These discrepancies may be attributable to the different patient populations, as some studies were performed in patients with acute myocardial infarction, while others included both patients with acute myocardial infarction and those with unstable angina.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with no-reflow phenomenon during PCI [10], positive coronary artery remodeling [11], clinical presentation feature such as acute coronary syndrome [12], high strain site [13] and localized endothelial dysfunction [14]. All of the above features are associated with worse clinical presentation or prognosis in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…6) Meanwhile, Hong, et al reported that the percentage of necrotic core volume through the entire culprit lesion segment was the only independent predictor of no reflow in ACS patients, as determined by multivariable analysis. 7) On the other hand, Nakamura, et al reported that the presence of a "marble-like" image, consisting mainly of fibrofatty and fibrous plaque, was significantly associated with angiographic no reflow in acute myocardial infarction (AMI) patients. 8) Similarly, Bae, et al also used multivariable analysis for AMI patients and found that fibrofatty volume over the entire culprit lesion length was the only independent factor for no reflow during primary PCI.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) Furthermore, spectral analysis of IVUS radiofrequency (RF) data has been employed to assess plaque composition, 5) however, the results to evaluate the culprit lesion with and without no reflow phenomenon have been controversial. [6][7][8][9] Here, we report the first clinical case of a new spectral similarity of RF IVUS signals for the evaluation of the culprit plaque characteristics in a patient with acute coronary syndrome and no reflow phenomenon.…”
Section: Urrently Percutaneous Coronary Intervention (Pci)mentioning
confidence: 97%